Feasibility of Growth Factor Agent Therapy in Repairing Motor Injury - Tan, Qiaoyin; Li, Jiayu; Liu, Yuwen; Zhu, Xiaojuan; Shao, Weide (Frontiers in Pharmacology, 2022)
Growth factors, with the activity of stimulating cell growth, play a significant role in biology, medicine, and exercise physiology. In the process of exercise, human tissues are impacted, making cells suffer damage. Growth factor can accelerate the repair of damaged cells and regulate the synthesis of protein, so biological prepara-tions of growth factors can be added to traditional therapies. A combination of growth factor biologics and conventional therapies may improve the efficiency of injury repair, but growth factor biologics may not produce any results. The feasibility of growth factor biologics in the treatment of motor injury was discussed.